2021
DOI: 10.1021/acs.jpclett.1c00434
|View full text |Cite
|
Sign up to set email alerts
|

Indentation Strengths of Zirconium Diboride: Intrinsic versus Extrinsic Mechanisms

Abstract: Zirconium diboride (ZrB 2 ) is an important ultrahigh-temperature ceramic, which exhibits outstanding mechanical properties and is widely used in extreme environments. Extensive experimental studies, however, have found that synthesized ZrB 2 specimens show widely scattered indentation hardness values ranging from 8.7 to 26 GPa. We have performed comprehensive stress−strain calculations of ZrB 2 to explore its structural and stress responses and found that ZrB 2 possesses an intrinsic indentation strength of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 68 publications
0
26
0
Order By: Relevance
“…using the CALYPSO [34][35][36] code. The underlying calculations on structural relaxation, ab initio molecular-dynamics (AIMD) simulations, electronic and elastic properties are performed with aid of the PBE exchange correlation functional [37][38][39], as implemented in the VASP package [33]. The valence space for Mg, Nb, H are 2p 6 3s 2 , 4s 2 4p 6 4d 4 5s 1 and 1s 1 , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…using the CALYPSO [34][35][36] code. The underlying calculations on structural relaxation, ab initio molecular-dynamics (AIMD) simulations, electronic and elastic properties are performed with aid of the PBE exchange correlation functional [37][38][39], as implemented in the VASP package [33]. The valence space for Mg, Nb, H are 2p 6 3s 2 , 4s 2 4p 6 4d 4 5s 1 and 1s 1 , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…CALYPSO software ( Wang et al, 2010 , 2012 ) was utilized to search the initial geometries of AuMg n ( n = 2–12) nanoclusters. CALYPSO can perform predictions of the energetically low-lying isomers structures at given chemical compositions and pressure for nanoclusters ( Lv et al, 2012 ; Zhao et al, 2019 ; Lu et al, 2020 ) in gas-phase and crystals ( Lu and Chen, 2020a , 2020b , 2021 ; Sun et al, 2020 ; Chen et al, 2021 ) via particle swarm optimization (PSO) algorithm. To search for as many low-lying energy isomers of AuMg n ( n = 2–12) nanoclusters as possible, the following strategy will be employed.…”
Section: Computational Methods Detailsmentioning
confidence: 99%
“…In the PSO methodology, we used 30 generations with each generation containing 30 structures to obtain around 900 configurations for each cluster size. Recent studies have revealed the PSO based approach in CALYPSO [85][86][87][88][89][90][91][92][93][94][95][96][97][98] to be highly efficient and precise in arriving at the ground state of clusters and chemical compounds. Following the PSO based optimizations, ten lowest energy configurations were reoptimized for each cluster with the help of B3LYP, TPSS and M06-L functionals and the TZVP basis set to find the ground state structure.…”
Section: Computational Detailsmentioning
confidence: 99%